OVERCOMING ENERGY EFFICIENCY CHALLENGES IN C-RAN: A REVIEW OF RECENT ADVANCES AND SOLUTIONS - Taha Shahzad; Muhammad Awais; Furqan Zahid; Basit Ali; Khawaja Maaz-Ur-Rahman (Spectrum of Engineering Sciences, 2025)
Cloud Radio Access Networks (C-RAN) is one of the novel approaches to cell network architecture by centralizing baseband processing devices (BBUs) into cloud statistics facilities and dispensing far off radio heads (RRHs) at mobile web sites. While C-RAN supports aspects of higher scalability, flexibility and network management, it also creates significant large power-intake demanding scenarios due to its operation with multiple RRHs and the power-in-depth BBU pools. This paper examines the major challenges in realizing power efficiency in C-RAN with dynamic site traffic loads, idle power consumption as well as cooling requirements in central data centers. For example, we consider several alternative designs such as dynamic BBU pooling, sleep mode techniques for RRHs, AI-based visitors prediction, and integration of renewable sources of energy. Hence, based on such results, it can be inferred that strength consumption decreases significantly without degrading the community performance with such technologies, especially by implementing them at various layers of the network. This work concludes with some future research guideline on how to improve the energy efficiency of C-RAN in the scenario of 5G and previous networks.